'Remote' in the Eastern Caribbean : the Antigua-US WTO internet gambling case - Cooper, Andrew F. (The Centre for International Governance Innovation WaterlooCA, 2008)
Looks at the case brought to the WTO by Antigua, the Internet Remote Gambling Case which has challenged standard assumptions about the workings of the international trading system in the WTO context. Antigua claimed that the American government failed to live up to its commitment under GATS regarding 'recreational services'. Notes that while Antigua argued for fairness in the WTO system, the US adopted a prohibitionist attitude to internet remote gambling, citing domestic moral standards.